1972
DOI: 10.1111/j.1423-0410.1972.tb03466.x
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Leukocytes from Whole Blood and Erythrocyte Suspensions by Filtration through Cotton Wool

Abstract: Abstract. Using the filtration method described earlier, leukocytes were removed from units of fresh whole blood and erythrocyte suspensions (hematocrit 50%). After filtration, the units were stored for one or two weeks. Units of whole blood and erythrocyte concentrates were stored for periods up to three weeks, the leukocytes were then removed by filtration, and the units were stored for another week. During the storage period, the following parameters were measured: pH and concentrations of ATP + ADP, 2,3‐di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

1981
1981
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 8 publications
3
42
0
Order By: Relevance
“…The precise way in which the blood was to be prepared was not specified. Most centers gave "washed" leukocyte-poor blood, but a few used cotton-wool-filtered blood, which for all pracücal purposes IS leukocyte-free (Diepenhorst et al, 1972) As IS shown in Fig. 3, this prospective study confirmed the retrospective study with respect to the graft-protecting effect of one transfusion of leukocyte-poor blood.…”
Section: Blood Transfusionsupporting
confidence: 71%
“…The precise way in which the blood was to be prepared was not specified. Most centers gave "washed" leukocyte-poor blood, but a few used cotton-wool-filtered blood, which for all pracücal purposes IS leukocyte-free (Diepenhorst et al, 1972) As IS shown in Fig. 3, this prospective study confirmed the retrospective study with respect to the graft-protecting effect of one transfusion of leukocyte-poor blood.…”
Section: Blood Transfusionsupporting
confidence: 71%
“…It was found that most of the phenomena observed during leukocyte filtration experiments could be explained by a general mathematical formulation of the process [Eqs. (8) and ( superficial filtration velocity (cm . s- ') filter porosity in Diepenhorst model, Eq.…”
Section: Discussionmentioning
confidence: 99%
“…(8) and (9)], at least three filtration parameters, c, urnax and A, , should be solved independently. Since theoretical relations for these parameters in terms of the properties of the filter are not yet well developed, this can only be achieved by trial and error.…”
Section: Curve Fitting Experimentsmentioning
confidence: 99%
“…To further reduce the incidence of especially HLA (human leukocyte antigen) alloimmunization in poly-transfused and/or transplant patients, filters were developed to selectively reduce the leukocytes in the blood (table 1). This lead to a reduction in the formation of α-HLA antibodies in these frequently transfused patients and further reduced the number of febrile complications [10,11]. When analyzing the results from different studies across the world, it is important to realize that, although whole blood is not widely used anymore, all other types of erythrocyte products are considered 'the' standard erythrocyte product in some countries.…”
Section: Transfusion Productsmentioning
confidence: 99%